ANALISIS PENENTUAN HARGA JUAL BARANG DAN JASA TERHADAP TINGKAT LABA PADA BERLIAN BEAUTY CLINIC SAMARINDA - Suwardana, Arie; Asmapane, Set; Kurniawan, Indra Suyoto (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
Arie Suwardana, 2018 , Analysis of Determination of Selling Price of Goods and Services to Profit Level on Diamond Beauty Clinic Samarinda is guided by Set Asmapane as mentor I and Indra Suyoto Kurniawan as mentors II Berlian Beauty Clinic is a company engaged in the sale of goods and services with raw materials of medicines for beauty care and beauty services by a competent physician in the beauty care industry. Determination of selling price is one of important policy in a company. Diamond Beauty Clinic fluctuates every year, changing market prices, making it difficult to determine the selling price of the product, due to the sale price of the product using the market-based selling price, resulting in a decrease in revenue in 2014 and 2015.Researchers conduct activities to obtain a clear picture of how the determination of the selling price used by the company by comparing with the method of full costing through literature study, observation, and interviews. In this study, the authors try to recalculate the cost of basic costs of production issued by the company as a basis in determining the selling price by referring to the method of full costing. Costs incurred by the company that the authors calculate is consisting of the cost of raw materials, direct labor costs and factory overhead costs. In this research can be concluded that (1) Determination of selling price of goods and services by company still do calculation with simple method and still use assumption from company, Cost calculated not yet cover all expense, so that expected target not fulfilled. The company's targeted mark up by 40% of the cost of production after being analyzed and calculated by the full costing method occurs the total difference of the selling price in November amounted to Rp 6.086.284 and the selling price set by the company is too low (2) The level of profit earned by the company based on the selling price of goods and services experienced a difference with full costing method with gross profit difference in November 2017 of Rp 1,738,938, The difference is derived from the calculation of total production costs minus the total selling price of the product that has been added with a gross profit of 40% of the total cost of production targeted by the companyThe author gives advice should be in determining the selling price in order to use the full costing method because it describes the costs incurred by the company as a whole and not just an estimate.Keywords: Analysis, Selling Price, and Profit Rate